Editorial JeDEM Vol. 12, No. 2 (2020) - Judith Schossboeck; Noella Edelmann (JeDEM - eJournal of eDemocracy & Open Government, 2020)
The editorial from managing editors comprises information on the published articles as well as new information regarding the activities around JeDEM.